Dewetting of a sol-gel-derived thin film - Kwon, SJ; Park, JG (AMER CHEMICAL SOC, 2006)
We report on the dewetting of a thin film produced by the sol-gel method. In the early stages of dynamic morphological instability, the drying stress in the capillary wave model determines the linearly scaling behaviors of the characteristic wavelength with the initial film thickness and the square law dependence of the number density of the dewetted holes on the film thickness. These power law dependences are weaker than those observed in the case of the spinodal dewetting of a polymer thin film. The wavelength determined in the early stages also dominates the scaling behaviors of the average length of the sides and number density of the polygons and the diameter of the droplets of the dewetting pattern with the film thickness in the final stages of the dynamic instability. We also observed that further drying eventually induces wrinkles in the droplets, rim, and film, which have a characteristic wavelength that can be theoretically predicted.
Keywords: POLYMER-FILMS; X-RAY; SURFACES